Penerapan Model Pembelajaran Project Based Learning Untuk Meningkatkan Hasil Belajar IPAS Kelas IV C Melalui Media Misteri Box - Qonita Kurrotul Akyun; Bekti Wirawati; Mahyuni Rahayu (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Students often have difficulty understanding the concepts of Natural and Social Sciences (IPAS), especially at the elementary school level. This difficulty is caused by the lack of variety of learning methods that are capable and attract students to actively participate in learning activities. The aim of this research is to determine the improvement in learning outcomes of class IV C students in the elastic movement material in science and science lessons. This research applies the Project Based Learning (PjBL) learning model which uses Mystery Box media. This research uses the Classroom Action Research (PTK) method which consists of two cycles. The instruments used include pretest and posttest as well as observation sheets. The data was analyzed descriptively quantitatively to measure the increase in learning outcomes from one cycle to the next. The research results show that implementing PjBL with Mystery Box media improves student learning outcomes. In the first cycle, there was significant improvement, although some students had not reached the target. In the second cycle, learning outcomes continued to improve, with the majority of students reaching or exceeding the KKM. The percentage obtained from the pretest and posttest results was from 56.73% to 74.62%.